USING MODERN INTERACTIVE METHODS IN TEACHING ENGLISH TO A2 LEARNERS - Goziboeva Khosiyat Adkhamovna (Web of Journals Publishing, 2023)
The article is devoted to the importance of using modern interactive ways in order to improve students' interests in English language, and provides new methods for teachers to teach by using up-to-date technologies which can be an efficient sources in the current education system.
Keywords: methodological innovations, classroom atmosphere, reading a text, new strategies, activities, games, technologies, critical thinking.